2015
DOI: 10.5888/pcd12.140584
|View full text |Cite
|
Sign up to set email alerts
|

A National Asian-Language Smokers’ Quitline — United States, 2012–2014

Abstract: IntroductionUntil recently, in-language telephone quitline services for smokers who speak Asian languages were available only in California. In 2012, the Centers for Disease Control and Prevention (CDC) funded the national Asian Smokers’ Quitline (ASQ) to expand this service to all states. The objective of this study was to examine characteristics of ASQ callers, how they heard about the quitline, and their use of the service.MethodsCharacteristics of callers from August 2012 through July 2014 were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Half of callers to the nationwide ASQ heard about the service through print media. 20 The current study similarly found that half of callers were referred through media. Paid advertising in ethnic media is expensive; however, press releases (including where ASQ already purchased ads) resulted in earned (free) media mentions, articles, and features.…”
Section: Discussionsupporting
confidence: 66%
“…Half of callers to the nationwide ASQ heard about the service through print media. 20 The current study similarly found that half of callers were referred through media. Paid advertising in ethnic media is expensive; however, press releases (including where ASQ already purchased ads) resulted in earned (free) media mentions, articles, and features.…”
Section: Discussionsupporting
confidence: 66%
“…In a clinic serving Chinese immigrants in San Francisco that offered tobacco‐cessation services that included counseling, nicotine‐replacement therapy, and acupuncture, over 90% of patients chose to include acupuncture; inclusion of this traditional medicinal approach may have increased acceptability of cessation assistance . Although telephone quitlines are an effective smoking‐cessation tool, California was the only state in which they were available in Asian languages until 2012, when the service became available nationwide . In the first 2 years, almost 6000 callers have used this national resource.…”
Section: Selected Findingsmentioning
confidence: 99%
“…103 Although telephone quitlines are an effective smokingcessation tool, California was the only state in which they were available in Asian languages until 2012, when the service became available nationwide. 104 In the first 2 years, almost 6000 callers have used this national resource. 105 ) and also contributes to the development of independent risk factors, such as nonalcoholic fatty liver disease and type 2 diabetes.…”
Section: Risk Factors For Cancermentioning
confidence: 99%
“…The underuse of proven cessation methods may be explained by the dearth of culturally appropriate programs targeting this population 13 and access barriers to available smoking cessation services 14 - 16 . Current smoking cessation programs, which focus on Chinese communities such as Asian Smokers’ Quitline (ASQ), and communitybased services have limited population impact due to their low engagement rates 17 .…”
Section: Introductionmentioning
confidence: 99%